Using the Duolingo Application as a Vocabulary Learning Tool in Higher Education - Febrianti, Mariska; Rahmawati, Istiqomah Nur; Aisyah, Aisyah; Nasution, Awal Kurnia Putra; Aprianto, Agung (Journal International of Lingua and Technology, 2024)
The use of technology in education has grown rapidly in recent years. One of the increasingly popular language learning apps is Duolingo. This app provides an easy-to-use, interactive and free way to learn many languages, including foreign languages. This study aims to determine the use of the Duolingo application as a means of learning vocabulary in tertiary institutions. This study uses quantitative methods by collecting population and samples. The data obtained through the distribution of questionnaires. The questionnaire was created by using the Google form. The number of questions is 15 with the categories strongly agree, agree, disagree and strongly disagree. The study was conducted through surveys and interviews with a number of students who used Duolingo as a vocabulary learning tool. In addition, research also observes the effect of using this application by assessing students' learning progress after using Duolingo. The results of the study show that the Duolingo application makes a positive contribution to learning vocabulary in universities. Students say the app provides a fun learning experience and inspires them to keep practicing. The app's interactive features, such as play-based exercises, also help increase learning engagement and enhance student engagement. In addition, this research also shows that students' learning progress after using Duolingo increases significantly. Using this application provides flexible learning access and allows students to study anytime, anywhere according to their interests and schedule. In short, the use of the Duolingo application as a tool for learning vocabulary in tertiary institutions can be considered effective and useful. This application can be an interesting and effective alternative to improve students' understanding and fluency of vocabulary. However, it is important to continue researching and developing the use of this learning technology so that it can be optimized and adapted to the needs and characteristics of each educational institution